1999
DOI: 10.1016/s1074-5521(99)80049-0
|View full text |Cite
|
Sign up to set email alerts
|

A unique urinary constituent, 6-hydroxy-6-methyl-3-heptanone, is a pheromone that accelerates puberty in female mice

Abstract: The male house mouse excretes into its urine a large quantity of a volatile substance that has a unique lactol/hydroxyketone structure. This substance is capable of binding to the less volatile urinary constituents, such as proteins or peptides, and is active in puberty-acceleration bioassays. The controversies regarding the volatility of the puberty-accelerating pheromones can now be explained by considering a complex of volatile lactol/hydroxyketone and urinary proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 20 publications
2
92
0
Order By: Relevance
“…DHB and also HMH and SBT accelerated uterine growth in prepubertal female ICR(CD-1) mice to a level comparable to the effect of male urine (Novotny et al, 1999b). HMH also increased uterine weight in (SJL/J × SWR/J)F1 hybrid mice (Novotny et al, 1999a). Here, we showed that DHB, HMH and SBT accelerated vaginal opening in another mouse strain derived from the Swiss lineage (Lynch, 1969;Beck et al, 2000;Yalcin et al, 2010).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…DHB and also HMH and SBT accelerated uterine growth in prepubertal female ICR(CD-1) mice to a level comparable to the effect of male urine (Novotny et al, 1999b). HMH also increased uterine weight in (SJL/J × SWR/J)F1 hybrid mice (Novotny et al, 1999a). Here, we showed that DHB, HMH and SBT accelerated vaginal opening in another mouse strain derived from the Swiss lineage (Lynch, 1969;Beck et al, 2000;Yalcin et al, 2010).…”
Section: Discussionsupporting
confidence: 54%
“…Our characterization of volatile compounds in intact male-soiled and castrated male-soiled beddings by gas chromatography coupled to mass spectrometry revealed that the major androgen-dependent volatile compounds present in intact male-soiled bedding are DHB, HMH and SBT (Jouhanneau, 2014). These three compounds have also been detected in urine of male mice (Liebich et al, 1977;Novotny et al, 1984Novotny et al, , 1999aSchwende et al, 1986;Flanagan et al, 2011;Supplementary Figure 1 and Table 1). …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Characteristic urinary components found in M. domesticus are three dihydrofuran compounds (MW 126) originating from a puberty accelerating pheromone, 6-hydroxy-6-methyl-3-heptanone (Novotny et al, 1999) and its lactol form (see Table 1 for 5,5-dimethyl-2-ethyl-4,5-dihydrofuran, Z-5,5-dimethyl-2-ethylidenetetrahydrofuran, E-5,5-dimethyl-2-ethylidenetetrahydrofuran). These three furan derivatives were present in male M. spicilegus at the level comparable to the M. domesticus data reported earlier (Harvey et al, 1989;Novotny et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Reagents and Analytical Methods All compound identifications were verified through the authentic standards whenever available. Standard compounds were either purchased from Aldrich Chemical Company (Milwaukee, WI) or synthesized in our laboratory according to the previously described synthetic methods for dehydro-exo-brevicomin (Wiesler et al, 1984), sec-butyl-4,5-dihydrothiazole (North andPattenden, 1990) and 6-hydroxy-6-methyl-3-heptanone (Novotny et al, 1999). Twister™ stir bars (10 mm in length, 0.5 mm film thickness, 24-μL polydimethylsiloxane (PDMS) volume) were used as the sorptive extraction devices.…”
Section: Methodsmentioning
confidence: 99%